Changes in fruit sugar concentrations in response to assimilate supply, metabolism and dilution: a modeling approach applied to peach fruit (Prunus persica) - Genard, M.; Lescourret, F.; Gomez, L.; Habib, R. (Tree physiology, 2003)
The influence of assimilate supply, metabolism and dilution on sugar concentrations in the mesocarp of peach (Prunus persica (L.) Batsch) fruit during the main stage of fruit enlargement was analyzed with the SUGAR model of Génard and Souty (1996). The model predicts the partitioning of carbon into sucrose, sorbitol, glucose and fructose in the mesocarp of peach fruit. Based on measured data and the model, we determined values for the relative rates of sugar transformation. These rates were constant, varied with time or varied with relative fruit growth rate, depending on the type of sugar. Equations were derived to describe these rates and incorporated into the SUGAR model. The model simulated the effects of changing assimilate supply and fruit volume on sugar concentrations. The set of equations for the SUGAR model was rewritten to include the three components influencing sugar concentrations: assimilate supply, metabolism and dilution. The sugar types differed in sensitivity to these components. Sucrose was highly sensitive to changes in assimilate supply and to the dilution effect; it was not subject to intense metabolic transformation. Sorbitol was the most important carbohydrate in fruit metabolism, which explains why the sorbitol concentration was always low despite the strong positive effect of assimilate supply. The reducing sugars constituted a transitory storage pool and their concentrations were closely related to metabolism.